Carbonic Anhydrase II Deficiency: A Rare Case of Severe Obstructive Sleep Apnea - Emanuela di Palmo; Marcella Gallucci; Elena Tronconi; Rosalba Bergamaschi; Salvatore Cazzato; Claudio La Scola; Giampaolo Ricci; Andrea Pession (Frontiers Media S.A., 2018)
The term osteopetrosis describes a group of rare hereditary diseases of the skeleton, characterized by an increase in bone density, caused by a defect in the development or function of osteoclasts. It comprises a clinically and genetically heterogeneous conditions ranging from infantile onset life-threatening forms to mildest adult onset forms. "Malignant" osteopetrosis is characterized by bone fragility, short stature, compressive neuropathies, hypocalcaemia, pancytopaenia. The deficiency of carbonic anhydrase II causes a moderate form, presenting classically as a triad of osteopetrosis, renal tubular acidosis (RTA), and cerebral calcification. This condition leads to specific craniofacial dysmorphisms associated with upper airway obstruction that may result in obstructive sleep apnea. Herein we report a case of osteopetrosis with RTA associated with severe OSAS successfully treated with continuous positive airway pressure (CPAP).